2004
DOI: 10.1128/mmbr.68.3.538-559.2004
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Microbiology: Tools, Technologies, and Applications

Abstract: The field of microbiology has traditionally been concerned with and focused on studies at the population level. Information on how cells respond to their environment, interact with each other, or undergo complex processes such as cellular differentiation or gene expression has been obtained mostly by inference from population-level data. Individual microorganisms, even those in supposedly “clonal” populations, may differ widely from each other in terms of their genetic composition, physiology, biochemistry, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
316
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(332 citation statements)
references
References 276 publications
0
316
0
5
Order By: Relevance
“…In these engineered bacteria, 54 the two components of the regulatory device under study 55 (Ps→xylS/Pm→GFP) are thereby designed adjacent to where Ps-xylS and Pm-GFP are separated. The data 10 shown in Supplemental Figure S3 indicated that both 11 strains are virtually indistinguishable as no significant dif-12 ferences were noticed in either physical quality. Once this 13 was clarified, we repeated with strain P. putida KT-BGS 14 the same induction experiment with 3MBz that was done 15 previously with the reference P. putida mt-2-Pm.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In these engineered bacteria, 54 the two components of the regulatory device under study 55 (Ps→xylS/Pm→GFP) are thereby designed adjacent to where Ps-xylS and Pm-GFP are separated. The data 10 shown in Supplemental Figure S3 indicated that both 11 strains are virtually indistinguishable as no significant dif-12 ferences were noticed in either physical quality. Once this 13 was clarified, we repeated with strain P. putida KT-BGS 14 the same induction experiment with 3MBz that was done 15 previously with the reference P. putida mt-2-Pm.…”
mentioning
confidence: 85%
“…10 However, the range and intensity of expression noise of 11 given promoters appears in some cases as an adaptive 12 trait that frames the dynamic properties of promoter acti-13 vation [7][8][9]. The onset of single-cell technologies [10][11][12] 14 has shed some light on the various mechanisms behind 15 noise generation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods such as serial dilution (Zhang, et al, 2006), micromanipulation (Kvist, et al, 2007;Hongoh, et al, 2 2008), laser capture microdissection (Navin, et al, 2011), Raman tweezers (Brehm-Stecher & Johnson, 2004;Huang, et al, 2009) and microfluidics (Marcy, et al, 2007;Blainey, et al, 2011) have also been used effectively to separate cells prior to genetic or genomic analysis. However, for characterizing uncultivated symbionts these methods fall short of FACS in a number of ways.…”
Section: Introductionmentioning
confidence: 99%
“…Although the capacity to detect cell-specific nucleic acids without the need for culture may be considered an advantage of such acellular techniques, it is not without cost. The individual cell is the "...fundamental unit of biological organization..." (16,17). Additional layers of information are therefore intrinsically linked to the "granular" or corpuscular nature of microbes.…”
Section: Introductionmentioning
confidence: 99%